Influence of restorative margins position on one‐stage laser‐microgrooved implants‐supported single screwed crowns: A clinical, biochemical, and microbiological analysis. (26th November 2018) - Guarnieri, Renzo; Di Nardo, Dario; Gaimari, Gianfranco; Miccoli, Gabriele; Testarelli, Luca
Abstract: Aim: To clinically, biochemically, and microbiologically evaluate the influence of crown margins position on one‐stage laser‐microgrooved implants. Materials and Methods: Twenty‐one‐stage titanium implants with a laser‐microgrooved collar surface, supporting screwed, single crown restorations, were placed in 20 partially edentulous patients and evaluated. Clinical parameters included modified plaque index, modified gingival index, peri‐implant probing pocket depth, bleeding on probing, and distance between implant shoulder and mucosal margin. The parameters were recorded at baseline (crowns delivery) and at every 6‐month recall visit, until the end of the 3 years follow‐up period. At the same time intervals, radiographic marginal bone levels were assessed at the mesial and distal aspect of the implant sites. For biochemical analysis, the volume of the peri‐implant sulcus fluid, and its levels of interleukin‐1beta (IL‐1β), interleukin‐6 (IL‐6), and of tumor necrosis factor‐α, were utilized to evaluate the peri‐implant health conditions at the end of the 3‐year follow‐up period. At the same time, microbiological analysis, including the concentration of five putative periodontal pathogens ( Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Treponema denticola, and Tannerella forsythensis ), were assessed. The crown margins positions were classified into four groups (A = intracrevicular position >2 mm, B = intracrevicular position ≤2 mm/<1 mm, C = intracrevicular position ≤1 mm/<0 mm, and D = extracrevicular position), and the biochemical, and microbiological parameters were evaluated at 3 years. Results: No statistical differences of clinical and biochemical parameters were found between the four groups. In group A, compared to groups B, C, and D, a statistically significant higher concentration of putative periodontal pathogens was found. Conclusions: Results showed that the intracrevicular deeper position of the restoration margin does not influence the clinical and biochemical peri‐implant parameters. The deeper position of the crown margin is associated with a greater amount of putative periodontal pathogenic microflora colonization.